Meiotic chromosome behavior of three species of Solanum of north-east India - AJOY KUMAR DAS; MAINA BORAH (International Journal of Pharma and Bio Sciences, 2019)
Study of chromosome behavior during meiosis is very important as it insights the stability and integrity of the genome as well as the genetic variation of a species. In the present investigation, meiotic chromosome behavior of three important non-tuberous wild species of the genus Solanum (Viz. S. torvumSwartz., S. ferox Linn. and S. indicum Linn.) available in North East India. Apart from their high medicinal and nutritional value, the cytological study of such wild non-tuberous Solanum species of this region is very limited. We have first reported the meiotic chromosomal behavior for these three wild species of Solanum available in this region. The main aim of our study was to find out any abnormality in homologolous pairing and recombination of the chromosomes in all the three species. Here, all the species showed regular meiotic division. The haploid chromosome exhibited normal rod-shaped and ring-shaped bivalents. Distinct variation in the frequencies of chiasma per nucleus as well as per bivalent was observed in all the species under study. n = 12 chromosomes were observed in the pollen mother cells of each species. This investigation reveals genomic stability as well as interspecific variation among the studied species which might facilitate further genetic improvement of these species.